2003
DOI: 10.1103/physrevb.67.014209
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding crossing of dielectric resonances in three-component composites

Abstract: We extend Green's function formalism to a three-component network by introducing a difference admittance ratio ϭ(⑀ 2 Ϫ⑀ 0 )/(⑀ 1 Ϫ⑀ 0 ). Using the formalism, we investigate the dielectric resonance of various disordered composites, and find that the neighboring resonances avoid crossing when parameter is varied in the interval (0,2͔. It is also shown that the geometric disorder and colored disorder lead to the avoiding of crossing of dielectric resonances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Also, for graded component, (r) is a continuous function, which will cover the full region, i.e., −∞ (r) ∞. Therefore, the eigenvalues s n , which depend on the continuously graded microstructure (r), do not lie within the interval [0, 1] but extend to −∞ s n ∞ as first pointed by Gu and Gong [33] for three-component composites case. However, eigenvalues s n still lie in [0, 1] for 0 (r) 1.…”
Section: Spectral Representation For Understanding the Effective Dielmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, for graded component, (r) is a continuous function, which will cover the full region, i.e., −∞ (r) ∞. Therefore, the eigenvalues s n , which depend on the continuously graded microstructure (r), do not lie within the interval [0, 1] but extend to −∞ s n ∞ as first pointed by Gu and Gong [33] for three-component composites case. However, eigenvalues s n still lie in [0, 1] for 0 (r) 1.…”
Section: Spectral Representation For Understanding the Effective Dielmentioning
confidence: 99%
“…We would also like to mention that the extension of the Bergman-Milton spectral representation to the threecomponent composite can be made by taking into account various approaches [31][32][33].…”
Section: Original Derivationmentioning
confidence: 99%
“…Previously, multiple resonance of surface plasmon has been reported in the nanocrescent and C-type structures [22,23] It is found that near η = 2.8 the avoiding of crossing and mode transfer phenomena between branch 41 and branch 42 appear. We noted the same phenomena of dielectric resonance occurring in the quasistatic limit [20,24]. When η is very large, the resonant dielectric permittivities of both nanostrips go beyond the optical frequency region and are of limited practical use in optics.…”
Section: (C)mentioning
confidence: 88%
“…where C = C 1 ∪ C 2 denotes the cluster subspace, and η = ( 2 − 0 )/( 1 − 0 ) is called the difference permittivity ratio [20]. In the subspace C 1 or C 2 , 1 (r, ω) or 2 (r, ω) is simplified as 1 (ω) or 2 (ω).…”
Section: Green Matrix Methods For Two-component Subwavelength Structuresmentioning
confidence: 99%
“…It is found that near η = 2.8 the avoiding crossing and mode transfer phenomena between branch 41 and branch 42 appear. We note as well that within the quasistatic limit the same phenomenon of dielectric resonance occurs [51,52].…”
Section: Plasmon Control Through Binary Metallic Nanostrcuturesmentioning
confidence: 98%